2018
DOI: 10.1038/s41388-018-0611-7
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitors of ribosome biogenesis repress the growth of MYCN-amplified neuroblastoma

Abstract: Abnormal increases in nucleolar size and number caused by dysregulation of ribosome biogenesis has emerged as a hallmark in the majority of spontaneous cancers. The observed ribosome hyperactivity can be directly induced by the MYC transcription factors controlling the expression of RNA and protein components of the ribosome. Neuroblastoma, a highly malignant childhood tumor of the sympathetic nervous system, is frequently characterized by MYCN gene amplification a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
47
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(57 citation statements)
references
References 42 publications
10
47
0
Order By: Relevance
“…Finally, SOX11 repressed targets are enriched for gene sets involved in translation initiation, ribosome hyperactivity and mRNA processing, which is indicative of an enhanced ribosome biogenesis response as previously reported in MYCN driven NB 21 (Fig. 4c).…”
Section: The Sox11 Regulated Transcriptome Is Involved In Epigenetic supporting
confidence: 77%
“…Finally, SOX11 repressed targets are enriched for gene sets involved in translation initiation, ribosome hyperactivity and mRNA processing, which is indicative of an enhanced ribosome biogenesis response as previously reported in MYCN driven NB 21 (Fig. 4c).…”
Section: The Sox11 Regulated Transcriptome Is Involved In Epigenetic supporting
confidence: 77%
“…Inhibition of E2F1 suppressed neuroblastoma progression [23]. Inhibition of ribosome singling pathway was also a promising strategy in neuroblastoma treatment [24]. However, the functions and prognosis of ARMC6, DCTPP1, EIF4G1, ELOVL6 and FBL in neuroblastoma were not reported.…”
Section: Discussionmentioning
confidence: 99%
“…In overview, these results indicate a clear and an almost complete breakdown of the ribosome and the spliceosome pathways, which consequently might explain the decrease of cell proliferation. It has been reported that repressing or perturbing the ribosome biogenesis decreases the growth of the cells [42], and/or even could drive cells into senescence [43].…”
Section: Discussionmentioning
confidence: 99%